2023
DOI: 10.1111/jerd.13053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross‐polarization filters on the trueness of colors obtained with a single‐lens reflex camera, macro lens, and a ring flash

Abstract: ObjectiveTo investigate the effect of cross‐polarization filters on the colors of shade tabs obtained with a digital single‐lens reflex (DSLR) camera, macrolens, and a ring flash.Materials and MethodsDigital images of four shade tables (1M1, 3L2.5, 3R2.5, and 5M3) from the VITA Toothguide 3D‐Master shade guide were taken using a DSLR camera, 100 mm macrolens, and ring flash with two different cross‐polarizing filters (Polar_eyes and Filtropolar), and without (Nonpolarizer; n = 7). The CIE L*a*b* color coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Although the use of images is not a validated method for color measurements, previous studies have shown that standardizing image acquisition and correcting white balance using a neutral gray card can yield reliable results comparable to those obtained with spectrophotometers. [17][18][19] Another important consideration is the conversion of RGB values to CIELAB color coordinates, which depends on factors like the illuminant and observer angle. 20,24 The choice of an appropriate illuminant was a key parameter in our study, as we aimed to evaluate the color match of single-shade composites to the surrounding substrate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the use of images is not a validated method for color measurements, previous studies have shown that standardizing image acquisition and correcting white balance using a neutral gray card can yield reliable results comparable to those obtained with spectrophotometers. [17][18][19] Another important consideration is the conversion of RGB values to CIELAB color coordinates, which depends on factors like the illuminant and observer angle. 20,24 The choice of an appropriate illuminant was a key parameter in our study, as we aimed to evaluate the color match of single-shade composites to the surrounding substrate.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to ensure accurate color representation in the photographs to obtain reliable results, like those using devices specifically designed for color assessment (e.g., colorimeters). Although the use of images is not a validated method for color measurements, previous studies have shown that standardizing image acquisition and correcting white balance using a neutral gray card can yield reliable results comparable to those obtained with spectrophotometers 17–19 . Another important consideration is the conversion of RGB values to CIELAB color coordinates, which depends on factors like the illuminant and observer angle 20,24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is crucial to ensure that the colors in the images correctly represent the specimens for reliable results. To improve the reliability of the findings, using neutral gray references during image acquisition and ensuring proper illumination conditions is recommended [ 9 10 11 12 13 14 15 16 ]. Nevertheless, confirming the method’s accuracy is vital by comparing it to a validated technique, such as using a spectrophotometer [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%